2015
DOI: 10.1080/17470919.2015.1081401
|View full text |Cite
|
Sign up to set email alerts
|

Neural evidence for moral intuition and the temporal dynamics of interactions between emotional processes and moral cognition

Abstract: Behavioral and neurological studies have revealed that emotions influence moral cognition. Although moral stimuli are emotionally charged, the time course of interactions between emotions and moral judgments remains unknown. In the present study, we investigated the temporal dynamics of the interaction between emotional processes and moral cognition. The results revealed that when making moral judgments, the time course of the event-related potential (ERP) waveform was significantly different between high emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
50
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 79 publications
6
50
1
1
Order By: Relevance
“…This ERP effect was consistent with the behavioural findings that the reaction time differences between moral and immoral words only reached significance when the words were green rather than other colours. Previous studies have suggested that LPC is related to mental resource distribution41 and have considered it a representation of slow but controlled and elaborative processes, such as moral evaluation and reasoning313642. The larger LPC differences in green words in the present study showed that the conflict between immoral words and the metaphorical meanings of the colour green might lead people to devote more cognitive resources to completing moral evaluations and reasoning processes in late time windows.…”
Section: Discussionmentioning
confidence: 39%
See 3 more Smart Citations
“…This ERP effect was consistent with the behavioural findings that the reaction time differences between moral and immoral words only reached significance when the words were green rather than other colours. Previous studies have suggested that LPC is related to mental resource distribution41 and have considered it a representation of slow but controlled and elaborative processes, such as moral evaluation and reasoning313642. The larger LPC differences in green words in the present study showed that the conflict between immoral words and the metaphorical meanings of the colour green might lead people to devote more cognitive resources to completing moral evaluations and reasoning processes in late time windows.…”
Section: Discussionmentioning
confidence: 39%
“…Recently, neuroscientists demonstrated that there are many factors involved in moral processes (such as emotion28293031, culture32, and individual dispositions33) and identified the complex neural mechanisms underlying these factors. However, the neural mechanism responsible for the metaphorical connection between colours and moral concepts remains unknown.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In such studies, participants were recorded while processing morality-related words (e.g., Yang, Luo, & Zhang, 2017), behaviors (e.g., Yang, Li, Xiao, Zhang, & Tian, 2014), and images (e.g., Decety & Cacioppo, 2012), often in direct comparison to core disgust-related stimuli (e.g., Yang et al, 2014Yang et al, , 2017. Taken together, the extant ERP literature on morality is somewhat mixed: across this work, various researchers have observed morality-related changes in amplitudes in the N1 (Gui, Gan, & Liu, 2016;Yoder & Decety, 2014), N180 (successful versus attempted harm/help; Gan et al, 2016), recognition potential (versus neutral words; Yang et al, 2017), P200 (shame versus guilt; Zhu et al, 2019); P300 (versus neutral behaviors; Yang et al, 2014), N400 (versus neutral words; Luo et al, 2013), and late positive potential (LPP; Gui et al, 2016;Leuthold, Kunkle, Mackenzie, & Filik, 2015).…”
Section: The Time-course Of Moral Perception: An Erp Investigation Ofmentioning
confidence: 91%